SUSTAINABLE DEVELOPMENT AND ENERGY SECURITY - Adina TATAR; Dragos PASCULESCU; Florin Gabriel POPESCU; Teodora LAZAR (Fiabilitate şi Durabilitate)
This paper makes a presentation of the energy system in the context of energy security and the positioning of Romania, in the current conditions, when the international energy markets are in a continuous and complex change. Romania has the advantage of having its own sources of primary energy, being able to achieve a balanced energy mix, in electricity production, between the existing energy resources. The current priorities of the energy sector are correlated with those of the European Union, with the effort to limit the consequences of climate change, and to carry out activities in the sense of the sustainable development of society.